L'emploi du temps ou l'écriture labyrinthique - El Mourad, Dalia (Amaltea. Revista de Mitocrítica, 2009)
The literature of the twentieth century proposes an infinity of mythical recurrences due on one hand to the symbolic value of the mythical account and on the other hand to its structuring value. Thus, the text of L’Emploi du temps by Michel Butor (1956) which reiterates the myth of the labyrinth, sees itself strongly as much impregnated by the “semantic thickness” of the myth such as Gilbert Durand conceives it, that by its inherent structure which is used as basic structure for the novel. The myth of the labyrinth is reflected on the town of Bleston, making it an allegory of the mythical maze in which Jacques Revel loses himself. To escape this infernal city, Revel undertakes the construction of an account whose writing will take an increasingly labyrinthian aspect. The myth of the labyrinth “language preexistent to the text, but diffuse in the text” (Brunel 1992: 61), transforms the “account of an adventure” into the “adventure of an account” (Dällenbach 1997: 154). The novel thus proves to be a permanent research of the exit of the maze, but this search appears to be abortive since the modern novel of the twentieth century wants to be the reflection of this unexhausted and inexhaustible research.